Neo-Splicetopes in Tumor Therapy: A Lost Case? - Kloetzel, Peter M. (Frontiers in Immunology, 2022)
The observation that tumor patient derived T cells effective in adoptive T cell therapy are directed against spliced epitopes generated by ligating two distant cleavage products in a reverse proteasomal proteolysis reaction raised some hopes with regard to a general therapeutic and immune relevance of spliced epitopes. Concomitantly, the identification of spliced peptides was also the start of a controversy with respect to their frequency, abundancy and their therapeutic applicability. Here I review some of the recent evidence and discussions raising severe doubts on the immune relevance of spliced peptides. In light of published data, it therefore seems mandatory that before discussing a possible application of tumor neoantigen derived spliced epitopes as targets for adoptive T cell tumor therapy their cell surface expression in the context of HLA-1 proteins has to be unequivocally verified.